Biodegradation and decolorization of methylene blue, reactive Black-5, and toluidine blue-O from an aqueous solution using the polyphenol oxidase enzyme - Uddin, Jalal; Idrees, Muhammad; Ahmed, Humam; Batool, Saima; Rahman, Tanzeel Ur; Mehmood, Shahzil; Tanoli, Asad Khan; Muhsinah, Abdullatif Bin; Ullah, Hidayat; Musharraf, Syed Ghulam (Frontiers in Sustainable Food Systems, 2024)
In this study, polyphenol oxidase (PPOs) copper-containing enzyme was extracted from the selected agricultural food products i.e., Mangifera Indica (L.), Solanum tuberosum (L.), and Luffa cylindrica (L.), which has efficiently degrade degrades the azo dyes (Methylene blue, Reactive black-5, and Toluidine Blue-O) into less toxic compounds. After preparing the dye solution at various concentrations, the enzyme PPOs extracted with phosphate buffer were incubated with it for two hours. The percent decolorization rate was estimated by taking the unprocessed dye solution. The degraded products were characterized by UV-vis and FT-IR. All sets of experiments followed pseudo-first-order kinetics. The highest kinetic degradation rate constant was observed kt = 0.0213 min─1 (R2 = 0.9258) and kt = 0.0244 min─1 (R2 = 0.7627) in reactive black-5 by Mangifera Indica (L.) and Solanum tuberosum (L.), respectively. The enzyme extracted from the Solanum tuberosum (L.) peel decolorized Reactive black-5 and Toluidine Blue-O dyes at greater quantities, i.e., 83.29% and 70.84% with reaction times 120 and 90 min, respectively.